Produção e qualidade pós-colheita de couve-flor em função de doses de potássio em cobertura - Godoy, Amanda Regina; Salata, Ariane da Cunha [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Evangelista, Regina Marta [UNESP]; Kano, Cristiaini; Higuti, Andréa Reiko Oliveira [UNESP] (My University, 2012)
This paper aims to evaluate the effect of rates of potassium in top dressing on yield and quality of cauliflower of the cultivar Teresópolis Gigante. The experiment was conducted at São Manuel Experimental Farm of UNESP/FCA, from April to August 2006. Five treatments (0; 50; 100; 150 and 200 kg ha-1 of K2O in top dressing) were evaluated with a randomized complete block design involving five replications and ten plants per plot. At the harvest, evaluations were made in the number of leaves per plant, curd diameter and average weight; and the postharvest characteristics evaluated were pH, titratable acidity, level of soluble solids, reducing sugars, vitamin C and potassium content. It was observed that the rates of potassium did not influence these characteristics, showing that the application of this nutrient in top dressing is probably not necessary when fertilization occurs at planting, despite the existing recommendations for the crop.

O objetivo deste trabalho foi avaliar o efeito de doses de potássio em cobertura na produção e qualidade de couve-flor cultivar Teresópolis Gigante. O experimento foi desenvolvido na Fazenda Experimental São Manuel, pertencente à UNESP/FCA, no período de abril a agosto de 2006. Foram avaliados cinco tratamentos (0; 50; 100; 150 e 200 kg ha-1 de K2O em cobertura), no delineamento experimental de blocos casualizados, com cinco repetições e dez plantas por parcela. No momento da colheita, avaliou-se o número de folhas por planta, o diâmetro e a massa média da “cabeça”, e as características pós-colheita: pH, acidez titulável, teor de sólidos solúveis, açúcares redutores, vitamina C e teor de potássio. Observou-se que as doses de potássio em cobertura não influenciaram as características avaliadas, demonstrando que, provavelmente, não é necessária a aplicação desse nutriente em cobertura quando se faz a adubação de plantio, apesar das recomendações existentes para a cultura.
Yield and postharvest quality of cauliflower according to rates of potassium in top dressing
Keywords: Brassica oleracea var. botrytis; Potassium fertilization; Physicochemical characteristics; Brassica oleracea var. botrytis; Adubação potássica; Características físico-químicas